Studying of Arabic Instruction System in Language Class and Non-language Class at Islamic State Junior High School of Tuban - Rouf, Muhammad (Al-Tadris: Jurnal Pendidikan Bahasa Arab, 2017)
Islamic State Junior High School of Tuban is an Islamic school where religious lessons are taught, including Arabic language subject. It has three main programs: Language Program, Mathematic and Science Program, and Social Science Program. Students at language department learn Arabic language matter more than students at other class. In fact, students at natural and social science class that learn Arabic language more little, could outperform students achievement in language class. The data of more superiority students at non language class than students at language class is talked by teacher of Arabic language.  The purpose of this research is to determine how developing curriculum in language and non-language classes. This research used a qualitative and descriptive method. Data were collected by observation, interview and documentation. The results, from the research, aren’t suitable with the purpose that was planned.. So that, all programs that have been set up don’t walk maximumly as expected.